Unravelling the impacts of western-style diets on brain, gut microbiota and cognition. (September 2021) - Kendig, Michael D.; Leigh, Sarah-Jane; Morris, Margaret J.
Highlights: Cognition can be impaired by obesity and diets high in fat and sugar across species. Intermittent consumption of poor diets may be sufficient to impair cognition. Dietary and exercise interventions improve diet-induced cognitive deficits. Microbiome modifications improve diet-induced cognitive deficits in rodents. Adolescence, ageing and maternal obesity may represent windows of additional risk. Abstract: The steady rise in the prevalence of obesity has been fostered by modern environments that reduce energy expenditure and encourage consumption of 'western'-style diets high in fat and sugar. Obesity has been consistently associated with impairments in executive function and episodic memory, while emerging evidence indicates that high-fat, high-sugar diets can impair aspects of cognition within days, even when provided intermittently. Here we review the detrimental effects of diet and obesity on cognition and the role of inflammatory and circulating factors, compromised blood-brain barrier integrity and gut microbiome changes. We next evaluate evidence for changing risk profiles across life stages (adolescence and ageing) and other populations at risk (e.g. through maternal obesity). Finally, interventions to ameliorate diet-induced cognitive deficits are discussed, including dietary shifts, exercise, and the emerging field of microbiome-targeted therapies. With evidence that poor diet and obesity impair cognition via multiple mechanisms across the human lifespan, the challenge for future research is to identify effective interventions, in addition to diet and exercise, to prevent and ameliorate adverse effects.